Bullying in Preschools: Prevention through Character Education from an Islamic Perspective - Majdy Kasheem; Mariam R. Arpentieva; Nurul Setiana; Petr V. Menshikov (Khalifa Journal of Islamic Education, 2025)
Prevention of bullying in preschool requires an approach that is appropriate to early childhood development. This study aims to analyze teachers’ efforts in preventing bullying through character education in early childhood from an Islamic perspective. A holistic multiple-case design (single unit of analysis) was used as the research design. Data were collected through observations, interviews with one principal and one experienced teacher, and an in-depth analysis of 21 reputable international scientific articles from several countries (United Kingdom, United States, Taiwan, Hong Kong, Indonesia, Saudi Arabia, Malaysia, Switzerland, Korea, Greece, and Sweden). Observations were conducted over twelve days on the teacher’s learning process, and in-depth interviews were carried out with the same teacher and the principal. All data were analyzed using the interactive qualitative data analysis model Miles & Huberman. The results show that teachers’ efforts in preventing bullying through character education in early childhood from an Islamic perspective are implemented through: (i) providing continuous understanding, good advice, and avoiding discrimination among peers; (ii) demonstrating positive attitudes; (iii) fostering empathy in children; and (iv) maintaining continuous communication between teachers and parents to jointly guide the children. These findings are consistent with behaviorist, constructivist, humanistic, and Islamic perspectives, all of which emphasize the importance of environmental support and direct experience in character building, which in turn has implications for preventing bullying in early childhood. The findings of this study can be used as one of the primary approaches for preventing bullying in early childhood.